Chemical Characteristics of Pineapple Jelly Drink (Ananas comosus) With the Addition of Carboxyl Methyl Cellulose - Khairia Latukau; Gelora Helena Augustyn; Syane Palijama (Jurnal Agrosilvopasture-Tech, 2022)
This study aims to determine the appropriate concentration of CMC addition in producing pineapple jelly drink with jelly drink chemical characteristics. This research was designed using Completely Randomized Design (CRD). which consists of one factor, namely the addition of CMC using 5 levels of treatment, namely: P0 = 0%, P1 = 0.5%, P2 = 1%, P3 = 1.5%, and P4 = 2%. The results showed that the addition of CMC had an effect on vitamin C, pH, and total dissolved solids with the following chemical characteristics, vitamin C 0.013%-0.02%, pH 3.95-4.55 and total dissolved solids 31.8°-43.8°brix.